Nipah Virus: A Neurotropic Zoonosis—From Molecular Biology to Clinical Manifestations and Translational Advances - Vignesh Mariappan; Heinz Feldmann (Viruses, 2026)
Nipah virus (NiV) is a single-stranded negative-sense RNA virus of the genus Henipavirus, family Paramyxoviridae. The World Health Organization has declared NiV a priority pathogen with a great public health risk due to its epidemic potential and lack of sufficient countermeasures. In humans, the virus causes Nipah viral disease (NVD), characterized by acute respiratory failure and/or encephalitis. Long-term assessments of NVD survivors have revealed persistent neurological dysfunction, including encephalopathy, cerebral atrophy, hyperintensities, ocular motor palsies, and dystonia. The entry of NiV into the central nervous system (CNS) is one of the critical and less studied aspects of its pathogenesis. NiV rapidly targets the olfactory epithelial cells in the nasal turbinate and subsequently infects neurons, allowing its spread into the CNS via axonal transport. In addition, infection of immature dendritic cells has been associated with severe CNS disease, supporting a potential role of hematogenous dissemination in neuroinvasion. Overall, understanding the molecular mechanism and the role of host factors in NiV neuropathogenesis is crucial for developing effective strategies to combat NVD. The present review delves into the neuropathogenic mechanism and immunobiology of NiV infection, as well as advancements in therapeutic modalities and vaccines against NVD.